EFISIENSI WAKTU PENGISIAN PERBEKALAN TERHADAP WAKTU TAMBAT KAPAL PERIKANAN PUKAT CINCIN DI TANGKAHAN PT. AGUNG SUMATERA SAMUDERA SIBOLGA KABUPATEN TAPANULI TENGAH PROVINSI SUMATERA UTARA - Juwita Insani Saragih; Syaifuddin '; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted in March 2013 in PT. ASSA Sibolga, NorthSumatra Province. The method used in this study is a survey of 15 purse seinevessels were chosen by purposive sampling. This study aims to determine thelevel of efficiency of the charging provisions. The result of this research can beinformation for who needthis file.The results showed that the efficiency of the charging provisions obtainedsix independent variables that affect the efficiency of the charging time is timewasted supplies, ice cubes, fresh water, the size of the vessel, the fishing trip andfuel. Based on the multiple linear regression analysis obtained values of r = 0.678and R2 = 67.8% (independent variable that diversity contributes to the diversity inthe values of supplies charging efficiency of 67.8%).Keywords: private port, purse seine, efficiency charging time supplies